Fertilizer Response by Two Species of Poplars on Initial Growth Parameters - Gangoo, S. A.; Mughal, A. H.; Makaya, A. S. (Indian Forester, 1997)
The paper presents a study on the growth behavior of two poplar species namely Populus deltoides and Populus nigra by giving different doses of fertilizer. The results indicate that N150 P 120 M20 is the best dose for Populus deltoides and N150 P 120 M10 is the best dose for Populus nigra for obtaining optimum height. Individually phosphorus and Nitrogen increases the height and diameter of both the species but there is no effect of fertilizer on root-shoot ratio and number of roots/plant in both the species.